Incidence of varicoceles in patients with ankylosing spondylitis evaluated by physical examination and color duplex sonography - Ozgocmen, S; Kocakoc, E; Kiris, A; Ardicoglu, A; Ardicoglu, O (Elsevier Science Inc, 2002)
Objectives. To assess the incidence of varicocele in ankylosing spondylitis (AS) in comparison to healthy age-matched controls. Methods. Twenty-one male patients with AS who were not taking disease-modifying antirheumatic drugs (eg, sulfasalazine, a well-known cause of drug-induced infertility) and age-matched healthy controls were evaluated with both physical examination and color duplex sonography for varicocele. The maximal vein diameters of pampiniform plexus and duration of reflux were recorded. Semen samples were also analyzed in both groups. Results. Patients with AS had a higher incidence of clinical varicoceles (52%) compared with the healthy age-matched controls (20%). On color Doppler examination, 12 patients (57%) had varicocele (3 bilateral and 9 on the left side) and 6 controls had varicocele on the left side. The patients with AS had significantly greater vein diameters of pampiniform plexus on the left and right side compared with the controls. Conclusions. The incidence of varicocele is increased in patients with AS, and its clinical relevance needs to be evaluated. (C) 2002, Elsevier Science Inc.
Keywords: Male-Infertility; Nitric-Oxide; Doppler Sonography; Spermatic Vein; Ultrasound; Sulphasalazine; Sulfasalazine; Diagnosis; Criteria